Technical and cost impact of differences in functional classification of road pavements - Chaves de Sousa, José Levi; Lima Maia, Camila; Vasconcelos , Sarah Denise; Lacerda de Oliveira, Francisco Heber (Revista ALCONPAT, 2024)
This work aims to analyze whether there are differences in the classification of the condition of a flexible road pavement using Continuous Visual Survey (LVC) and the Global Gravity Index (IGG). A section of a road paved with Asphalt Concrete was selected to assess the costs associated with each classification. Due to the longer time required for obtaining IGG, the analysis was limited to this section. The results revealed discrepancies in classifications and costs between the methods in the initial segments of the road. It was concluded that LVC provided better results than IGG, attributed to the inherent subjectivity of human assessment. Additionally, it was observed that the two methods complement each other in the functional analysis of road pavements.